2007
DOI: 10.1128/aac.01159-06
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Drug Nitazoxanide Inhibits the Pyruvate Oxidoreductases of Helicobacter pylori , Selected Anaerobic Bacteria and Parasites, and Campylobacter jejuni

Abstract: Nitazoxanide (NTZ) exhibits broad-spectrum activity against anaerobic bacteria and parasites and the ulcer-causing pathogen Helicobacter pylori. Here we show that NTZ is a noncompetitive inhibitor (K i , 2 to 10 M) of the pyruvate:ferredoxin/flavodoxin oxidoreductases (PFORs) of Trichomonas vaginalis, Entamoeba histolytica, Giardia intestinalis, Clostridium difficile, Clostridium perfringens, H. pylori, and Campylobacter jejuni and is weakly active against the pyruvate dehydrogenase of Escherichia coli. To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
213
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(227 citation statements)
references
References 36 publications
(69 reference statements)
6
213
1
Order By: Relevance
“…The molecular mechanism at the basis of the antiinfective activity of thiazolides is still not completely understood. In anaerobic organisms, such as Giardia intestinalis or anaerobic bacteria, nitazoxanide acts by inhibiting pyruvate:ferredoxin oxidoreductase (PFOR), an enzyme that is essential for the pathogen energy metabolism but that is not conserved in mammals (32). In the case of M. tuberculosis infection, inhibition of mTORC1 signaling and stimulation of autophagy were observed after thiazolide treatment, and the human quinone oxidoreductase NQO1 was proposed to be a drug target (33).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism at the basis of the antiinfective activity of thiazolides is still not completely understood. In anaerobic organisms, such as Giardia intestinalis or anaerobic bacteria, nitazoxanide acts by inhibiting pyruvate:ferredoxin oxidoreductase (PFOR), an enzyme that is essential for the pathogen energy metabolism but that is not conserved in mammals (32). In the case of M. tuberculosis infection, inhibition of mTORC1 signaling and stimulation of autophagy were observed after thiazolide treatment, and the human quinone oxidoreductase NQO1 was proposed to be a drug target (33).…”
Section: Discussionmentioning
confidence: 99%
“…Both C. jejuni and H. pylori utilize organic acids and amino acids as primary carbon and energy sources and rely on gluconeogenic pathways to provide the necessary intermediates for biosynthesis of cell wall material, vitamins, and nucleic acids (1,11,17,19,27,39). Other general features of these pathogens include (i) a strictly respiratory form of metabolism; (ii) reliance on molecular hydrogen as a key energy source (14,17,18,20,28); (iii) a preference for NADPH, rather than NADH, as the primary electron donor; and (iv) pyruvate oxidation via a reversible pyruvate:ferredoxin oxidoreductase (PFOR) (6,20). While the PFOR of H. pylori is composed of four subunits encoded by the porGDAB operon (20,23,37), the PFOR of C. jejuni is the product of a single gene, similar to the PFORs of anaerobic bacteria and amitochondriate protozoan parasites (21).…”
mentioning
confidence: 99%
“…Nitazoxanide is safe when administered orally and has extensive post-marketing demand by millions of adults and children (27). Nitozlides interfere with Pyruvate: Ferredoxin oxidoreductase (PFOR) enzymedependent electron transfer reactions, which are indispensable for anaerobic energy metabolism for anaerobic bacteria (28) Tizoxanide is another derivative of thiazolide and has been shown to be effective against Hepatitis B and C infections. Tizoxanide's mechanism of action on HCV replication in cell culture showed that it stimulates PKR.…”
Section: Discussionmentioning
confidence: 99%